FAKTOR FAKTOR SOSIAL EKONOMI KELUARGA BERHUBUNGAN DENGAN KEJADIAN GONDOK PADA MURID SD - Siti Madanijah; Ageng Basuki Hirmawan (Food and Nutrition Society of Indonesia, 2007)
The objective of this study is to identify the factors that affect the high prevalence of goiter among elementary school students in goiter endemic area. The specific objective are to identify the socio-economic characteristics of the sample family, to analyze food consumption related to goiter, to identify the variety of food contains of goitrogenic substances, to measure the iodium salt concentration, to analyze the correlation between mother knowledge about IDD, food consumption and the quality of salt with the goiter status. This research was designed with cross sectional study with purposive method. This research was conducted at Kabupaten Tasikmalaya, West Java from April to May 2005. The respondent consisted of 60 elementary school students, which 30 of them classified as normal group and the rest of them belong to the goiter group. The two sample groups were analyzing by the t-test and Mann Whitney test. The correlation variables were analyzed by the Spearman test. There were significant difference between the income on the normal group and the goiter group; the normal group had higher income than the rest. There were significant difference between the adequacy level of energy on the normal group (73.5%) and the goiter group (55.8%) and the average of the variety of goitrogenic food consumption. The Mann Whitney test showed there were also significant differences for the quality of salt. There were significant correlations between mother knowledge about IDD with the adequacy of iodium, and between the cases of goiter with the quality of salt consumed by the family. Intensive nutrition education of IDD is needed to improve the nutrition knowledge of the mothers, as well as the availability of the accessible iodized salt.